2018
DOI: 10.3324/haematol.2018.198655
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and prognostic factors in adult patients with secondary hemophagocytic lymphohistiocytosis not associated with malignancy

Abstract: Hemophagocytic lymphohistiocytosis is an overwhelming systemic inflammatory process that is life-threatening if not treated appropriately. We analyzed prognostic factors of secondary hemophagocytic lymphohistiocytosis excluding malignancy. In this retrospective study, we analyzed 126 adult cases between 2001 and 2017. Treatment was based on dexamethasone with or without etoposide and cyclosporine. Patients who achieved complete response at 4 weeks were defined as early-stable responders, those who failed to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
64
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 38 publications
(41 reference statements)
11
64
3
Order By: Relevance
“…Additionally, age is also an independent prognostic factor. Elderly patients had shorter survival time, in consonance with the results of other studies [13,29]. It may be due to senescent organs resulting in more severe organ dysfunction [24] or other comorbid illnesses affecting the outcomes of HLH.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Additionally, age is also an independent prognostic factor. Elderly patients had shorter survival time, in consonance with the results of other studies [13,29]. It may be due to senescent organs resulting in more severe organ dysfunction [24] or other comorbid illnesses affecting the outcomes of HLH.…”
Section: Discussionsupporting
confidence: 87%
“…Thrombocytopenia was considered as a consistent prognostic factor in HLH [13,[21][22][23][24]. Similarly, our results also found that platelet less than 39.5 × 10 9 /L was an independent risk factor of 30-day survival.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…If the scenario in question is indeed suspicious for HLH (eg, unexplained high‐fevers in an immunodeficient host or severe sepsis unresponsive to directed antimicrobial therapy), we may consider further directed testing such as measurement of soluble interleukin‐2 receptor level or bone marrow aspiration and biopsy (among other investigations). Of note, some prior studies have suggested that degree of hyperferritinemia may be predictive of mortality among HLH patients; however, among our cohort this relationship was not statistically significant …”
Section: Discussioncontrasting
confidence: 93%